PERBANDINGAN YIELD OBLIGASI KORPORASI PADA SEKTOR KEUANGAN - Fadila, Ardhiani (Ekonomi dan Bisnis, 2016)
Bonds as cheap funding alternative for company and investment instrument that gives fixed income for investor make movement and development for Indonesian capital market. A lot of company issues bonds as sources of funding and supported with an excellent rating capable for getting investor’s attractive for investing in bonds, especially in financial sector as the pillar economic growth in the country. Bonds issues that dominated in financial sector give interesting yield for investor. Comparative analysis of yield can be done for knowing the differences in yield for each rating that company has. This study analysis method is Paired Samples T-test using PASW Statistics 18. The result of this study shows that on average there are significant yield differences in bonds that have idA, idAA+, and idAAA rating. This study also shows that bonds with lower rating give higher yield and the yield of bonds in banking sub-sector higher compared with the yield of bonds in multi finance sub-sectors.